Improving skills utilisation in the UK - Some reflections on what, who and how? - Keep, E (Centre on Skills, Knowledge and Organisational Performance, 2016)
An earlier version of this paper was commissioned in 2014 by one of the UK governments as a ‘think piece’ to reflect on the importance of skills utilisation for policy development, and what more might be done to pilot new ways of addressing this issue. This version has been prepared for wider circulation. It is not intended to provide a comprehensive literature review on the topic. Those seeking such a review are directed to the report prepared by CFE for the Scottish Government (2008) and a report prepared for the OECD by Buchanan and colleagues (2010). The four national governments within the UK all face broadly similar economic and social problems, though the depth and scale of these problems varies within and between each nation. Among these policy challenges are a range of issues that relate to productivity, investment and the shape and ‘balance’ of the economy, as well as with the quantity and quality of employment, the structure of the labour market and the nature and management of the relationship between employer and employee (Keep, 2013; Keep and Mayhew, 2014). As will be suggested below, many of these policy problems are inter-related.